SARS-CoV-2 Switches ‘on’ MAPK and NFκB Signaling via the Reduction of Nuclear DUSP1 and DUSP5 Expression - Goel, Swati; Saheb Sharif-Askari, Fatemeh; Saheb Sharif Askari, Narjes; Madkhana, Bushra; Alwaa, Ahmad Munzer; Mahboub, Bassam; Zakeri, Adel M; Ratemi, Elaref; Hamoudi, Rifat; Hamid, Qutayba; Halwani, Rabih (Frontiers in Pharmacology, 2021)
Mitogen-activated protein kinases (MAPK) and NF-kappaB (NF-B) pathway regulate many cellular processes and are essential for immune cells function. Their activity is controlled by dual-specificity phosphatases (DUSPs). A comprehensive analysis of publicly available gene expression data sets of human airway epithelial cells (AECs) infected with SARS-CoV-2 identified DUSP1 and DUSP5 among the lowest induced transcripts within these pathways. These proteins are known to downregulate MAPK and NF-B pathways; and their lower expression was associated with increased activity of MAPK and NF-B signaling and enhanced expression of proinflammatory cytokines such as TNF-. Infection with other coronaviruses did not have a similar effect on these genes. Interestingly, treatment with chloroquine and/or non-steroidal anti-inflammatory drugs counteracted the SARS-CoV-2 induced reduction of DUSP1 and DUSP5 genes expression. Therapeutically, impeding this evasion mechanism of SARS-CoV-2 may help control the exaggerated activation of these immune regulatory pathways during a COVID-19 infection.